أثر أساليب التميز التنظيمي على الأداء السياقي - douli, souade (Finance and Business Economies Review, 2018)
This study aimed at finding the positive relationship between the methods of organizational excellence (training, empowerment, incentives) and contextual performance in all its dimensions within the economic institution (CASNOS). In this study we relied on the distribution of copies of a questionnaire in the institution under study. The social workers of the non-wage workers consisted of 46 workers of various levels of employment. We used a statistical program in spss version 22 to process the data and analyze the results. We found the hypothesis as a result of a close relationship between the methods of organizational excellence And contextual performance.